Securing the Internet of Things (IoT) Data Ownership - Vermanen Mikko; Naskali Juhani; Harkke Ville; Koskinen Jani (Germany, 2025)
As the commercial use of IoT (Internet of Things) technology keeps spreading rapidly, so does
the involvement of individuals as data sources. Thus, it is crucial to understand the nature and
implications of data property factors in the IoT context to enable organisations to apply
ethically sustainable practices when defining data ownership. The study is based on Richard
O. Mason's PAPA framework from 1986, in which the question of intellectual property rights
is described as one of the most complex issues we face as a society. Based on our findings, this
statement still applies in modern IoT ecosystems. In this paper, the ownership and control of
information is clarified on conceptual and practical levels. We investigate the topic from the
following three perspectives: 1) organisational level, 2) technical level, and 3) ethical
ownership. Furthermore, we offer development proposals for the current IoT protocols, aiming
to support defining data ownership.
Proceedings of the Conference on Technology Ethics 2023 - Tethics 2023